New records of two flap-headed gobies of genus Callogobius (Gobiiformes: Gobiidae) from Taiwan with an updated artificial key of Taiwanese congeners - Li, Hsien-En; Chen, I-Shiung (Zootaxa, 2025)
Herein, we give vouchered new records upon two Callogobius from Taiwan; they are C. shunkan Takagi, 1957 and C. stellatus McKinney & Lachner 1978b. These records represent the southward and northward extension of the species’ previous geographical distribution, respectively. Detailed descriptions of their morphology, sensory canal and papillae patterns, and fresh colorations are given, and an artificial dichotomous key to all 11 Callogobius species is also provided to aid in related research.